THE EFFECT OF TIKTOK LIVE SHOPPING USE AND DIGITAL PROMOTION STRATEGY ON CONSUMER ENGAGEMENT IN PANENJOAN VILLAGE CICALENGKA DISTRICT BANDUNG RECENCY - Sani Agisni; Bambang Sucipto (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The development of digital technology has encouraged businesses to utilize social media as a marketing tool, one of which is through TikTok's Live Shopping feature. However, the use of TikTok Live Shopping in semi-rural areas such as Panenjoan Village, Cicalengka District, Bandung Regency, has not been optimal, as indicated by low consumer engagement and unstructured digital promotion strategies. This situation indicates a gap between the potential use of TikTok Live Shopping and the expected level of consumer engagement. Therefore, this study aims to determine the effect of TikTok Live Shopping utilization and digital promotion strategies on consumer engagement. This study used a quantitative approach with a survey method, along with descriptive and verification analysis. The study population was consumers in Panenjoan Village who had participated in TikTok Live Shopping. The sample was determined using the Lemeshow formula, resulting in 100 respondents using a purposive sampling technique. Data collection was conducted using a Likert-scale questionnaire. Data analysis included validity tests, reliability tests, classical assumption tests, correlation tests, multiple linear regression analysis, coefficient of determination tests, and hypothesis testing using SPSS version 27. The results showed that the use of TikTok Live Shopping, digital promotion strategies, and consumer engagement were in the strong category. Partially, the use of TikTok Live Shopping and digital promotion strategies had a significant effect on consumer engagement. Simultaneously, these two independent variables also had a significant effect on consumer engagement. This study concluded that optimizing TikTok Live Shopping and implementing effective digital promotion strategies can increase consumer engagement in Panenjoan Village.